Ireland : Financial Sector Assessment Program: Technical Note-Financial Safety Net, Bank Resolution, and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Ireland regarding the financial safety net, bank resolution, and crisis management. The introduction of the 'single rulebook' for financial services regulation within the European Union and the establishment of the banking union have transformed the Irish framework for dealing with failing banks. The new regime reflects an EU-wide initiative to strengthen supervision, harmonize prudential rules, and establish a uniform bank resolution regime. The Bank Recovery and Resolution Directive has significantly strengthened the resolution regime in Ireland and the European Union. Significant progress has also been made on the banking union, although key aspects remain to be completed.